COMMENTS FROM THE RUSSIAN EXPERTS TO «RECOMMENDATIONS ON THE INFANT NUTRITION» PREPARED BY THE US SPECIALISTS - I.Ya. Kon'; T.E. Borovik; E.I. Prakhin; T.N. Sorvacheva; N.A. Korovina; E.M. Bulatova; N.E. Sannikova; A.V. Chuprova ("Paediatrician" Publishers LLC, 2007)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2007;6(1):111-114)